2021
DOI: 10.3390/sym13091714
|View full text |Cite
|
Sign up to set email alerts
|

A Fault Diagnosis and Prognosis Method for Lithium-Ion Batteries Based on a Nonlinear Autoregressive Exogenous Neural Network and Boxplot

Abstract: The frequent occurrence of electric vehicle fire accidents reveals the safety hazards of batteries. When a battery fails, its symmetry is broken, which results in a rapid degradation of its safety performance and poses a great threat to electric vehicles. Therefore, accurate battery fault diagnoses and prognoses are the key to ensuring the safe and durable operation of electric vehicles. Thus, in this paper, we propose a new fault diagnosis and prognosis method for lithium-ion batteries based on a nonlinear au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…In the Gauss-Newton, the sum of the squared errors is reduced by assuming the least squares function is locally quadratic in the parameters and finding the minimum of this quadratic. The Levenberg-Marquardt method acts more like a gradientdescent method when the parameters are far from their optimal value and acts more like the Gauss-Newton method when the parameters are close to their optimal value [31]. In order to ameliorate the Levenberg-Marquardt algorithm with respect to convergence time and approximation quality, we propose a new version of this algorithm, named the Levenberg-Marquardt backpropagation neural network (LM-BPNN).…”
Section: Methodsmentioning
confidence: 99%
“…In the Gauss-Newton, the sum of the squared errors is reduced by assuming the least squares function is locally quadratic in the parameters and finding the minimum of this quadratic. The Levenberg-Marquardt method acts more like a gradientdescent method when the parameters are far from their optimal value and acts more like the Gauss-Newton method when the parameters are close to their optimal value [31]. In order to ameliorate the Levenberg-Marquardt algorithm with respect to convergence time and approximation quality, we propose a new version of this algorithm, named the Levenberg-Marquardt backpropagation neural network (LM-BPNN).…”
Section: Methodsmentioning
confidence: 99%
“…[ 74 ] As one of the main characterization parameters, voltage usually behaves differently under various faults, so voltage abnormity including over voltage and under voltage may imply serious internal faults and need to be identified. [ 75–77 ] Besides, battery mechanical damage during cycling, such as electrolyte leakage [ 78 ] and electrode deformation (e.g., swelling, strain, stress, cracking), [ 79–81 ] are also required to be predicted to ensure proper battery composition.…”
Section: Battery Prognosismentioning
confidence: 99%
“…The advent of AI and ML technologies has facilitated the effective identification and prediction of battery issues with reasonable levels of effort. Qiu et al [16] have suggested a failure diagnostic and prognosis technique for lithium-ion batteries. This method relies on voltage prediction, which is achieved through the use of a nonlinear autoregressive with exogenous input (NARX) neural network.…”
Section: Literature Surveymentioning
confidence: 99%